Active elite rugby participation predicts alterations in cortical thickness. Issue 9 (12th August 2022) - Parker, Thomas; Zimmerman, Karl; Laverse, Etienne; Bourke, Niall; Graham, Neil; Hesle-Grave, Amanda; Zetterberg, Henrik; Kemp, Simon; Morris, Huw; Sharp, David
Abstract : Background: Rugby is a collision sport with high rates of head injury. The effect of rugby participation at the elite level on cerebral grey matter structure is unclear. Methods: Data from 44 active professional rugby players, including 21 acquired within one week of mild traumatic brain injury, and 47 healthy controls were analysed. Whole-cortex and region of interest analyses investigating the effects of rugby participation, sub-acute mild traumatic brain injury, and biomarkers of traumatic brain injury (fractional anisotropy, plasma neurofilament light and glial fibrillary acidic protein) on cortical thickness were performed. Plasma neurofilament light and glial fibrillary acidic protein concen- trations were measured using Single molecule array technology. Results: Whole-cortex analysis revealed evidence of lower right hemisphere precentral cortical thickness in non-injured rugby players compared to controls. In region of interest analyses, there was evidence rugby participation predicted lower cortical thickness in the inferior part of the precentral sulcus (right hemisphere). In the same region, there was evidence sub-acute mild traumatic brain injury predicted higher cortical thickness compared to non-injured players, and that plasma glial fibrillary acidic protein was positively associated with cortical thickness in players with sub-acute mild traumatic brain injury. No associations with neurofilament light concentration were found. Conclusion: We present evidence that elite rugby participation predicts alterations in cortical thickness. Larger scale study with prolonged follow-up to understand the clinical implications of these findings is warranted.